2005
DOI: 10.1111/j.1471-0528.2004.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA identification of fetal cells isolated from cervical mucus: potential for early non‐invasive prenatal diagnosis

Abstract: Objectives To develop a reliable method to isolate fetal cells for genetic diagnosis.Design Aspiration of cervical mucus from pregnant women in the first trimester.Setting Pregnant women were recruited before an elective termination of pregnancy.Population Sixty pregnant women (7 -10 weeks of gestation).Methods Fetal cells were isolated from aspirated cervical mucus of pregnant women using a combination of enzymatic digestion, fluorescent immunohistochemistry, micromanipulation and single-cell DNA allelic prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Finally, if methods for noninvasive prenatal diagnosis using cell-free fetal DNA isolated from maternal plasma [32] or fetal DNA from trophoblast cells in cervical mucus [33] become available for routine clinical use, their combination with array-CGH would truly revolutionize the practice of prenatal diagnosis. Importantly, all these noninvasive testing approaches are focused on the first trimester, and earlier diagnosis of fetal abnormalities is obviously preferred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, if methods for noninvasive prenatal diagnosis using cell-free fetal DNA isolated from maternal plasma [32] or fetal DNA from trophoblast cells in cervical mucus [33] become available for routine clinical use, their combination with array-CGH would truly revolutionize the practice of prenatal diagnosis. Importantly, all these noninvasive testing approaches are focused on the first trimester, and earlier diagnosis of fetal abnormalities is obviously preferred.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the conditions that are detected by array-CGH are not associated with advanced maternal age or other prenatal risk factors, and we suggest that once prenatal diagnosis by array-CGH is well validated, it will strengthen the case for offering prenatal cytogenetic diagnosis to all pregnant women regardless of their age or maternal serum and ultrasound screening results [30,31]. Because array-CGH can be performed on very small amounts of DNA with or without whole genome amplification [5 •• ], it may enhance the potential for success of prenatal diagnosis from noninvasively sampled fetal DNA, either as cell-free DNA from maternal plasma [32] or as fetal cells from the cervix [33]. Such noninvasive testing may one day replace current screening protocols as the standard of care for prenatal diagnosis of chromosomal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Based on such new data, the recommended number for procedurerelated risk counseling in the USA is now one in 300-400 individuals [12]. The procedure-related risk of CVS is comparable to that of amniocentesis [13]. Based, in part, on these updated numbers, the guidelines of the American College of Obstetricians and Gynecologists now state that all women should have the option of invasive testing, regardless of their personal risk for aneuploidy or other genetic conditions [12,14].…”
Section: Current Clinical Practice Of Prenatal Diagnosismentioning
confidence: 98%
“…Using monoclonal antibody of cytokeratin-7 to identify cells, the reported detection rate was 60%. Katz-Jaffe et al [67] identified fetal cell DNA from cervical mucus aspirates collected before terminations of pregnancy between 7 and 10 weeks. In this study, isolation of fetal cells was accomplished by simple digestion and fluorescent antibody identification followed by micromanipulation to retrieve appropriate cells and DNA allelic profiling to confirm the fetal origin.…”
Section: Cervical Collection Of Trophoblast Cellsmentioning
confidence: 99%